Reduced mismatch negativity predates the onset of psychosis. - Shaikh, M; Valmaggia, L; Broome, MR; Dutt, A; Lappin, J; Day, F; Woolley, J; Tabraham, P; Walshe, M; Johns, L; Fusar-Poli, P; Howes, O; et al. (2012)
BACKGROUND: Individuals with an "At Risk Mental State" have a 20-30% chance of developing a psychotic disorder within two years; however it is difficult to predict which individuals will become ill on the basis of their clinical symptoms alone. We examined whether mismatch negativity (MMN) could help to identify those who are particularly likely to make a transition to psychosis. METHOD: 41 cases meeting PACE criteria for the At Risk Mental State (ARMS) and 50 controls performed a duration-deviant passive auditory oddball task whilst their electroencephalogram was recorded. The amplitude of the MMN wave was compared between groups using linear regression. The ARMS subjects were then followed for 2 years to determine their clinical outcome. RESULTS: The MMN amplitude was significantly reduced in the ARMS group compared to controls. Of the at-risk subjects who completed followed up (n=41), ten (24% of baseline sample) subsequently developed psychosis. The MMN amplitude in this subgroup was significantly smaller across all three recording sites (FZ, F3 and F4) than in the ARMS individuals who did not become psychotic. CONCLUSION: Among those with the ARMS, MMN amplitude reduction is associated with an increased likelihood of developing frank psychosis.